ANALISIS PENDAPATAN ASLI DAERAH (PAD) DALAM UPAYA PELAKSANAAN OTONOMI DAERAH DI KABUPATEN BADUNG BALI - Taras, Tyasani; Sri Artini, Luh Gede (E-Jurnal Manajemen; Vol 6 No 5 (2017), 2017)
The c onsequence of run ning an autonomous region is that each region is required to increas e the sources of revenue for funding the government ’s implementation and further impro ving public service. This study aims to determine efficiency and effectiveness level of local taxes and determine their contributions in increasing local revenues in Badung regency in 2011-2015. This study uses descriptive quantitative analysis techniques. The data used in this study was obtained from the Central Bureau of Statistics and the Department of Revenue of Badung R egency. The result shows that the tax efficiency level of Badung regency in 2011-2015 as very efficient and the l ocal tax effectiveness level of Badung in 2011-2015 as very effective. The contribution of local taxes on local revenue is in excellent level . Badung regency’s government has been able to optimize and manage the local tax revenues well.
Keywords: effectiveness, efficiency, contributions, revenue, local taxes